Electrochemiluminescent sensor based on an aggregation-induced emission probe for bioanalytical detection. Issue 11 (5th May 2022) - Lv, Xiaoyi; Li, Yanping; Cui, Bo; Fang, Yishan; Wang, Lishi
Abstract : In recent years, with the rapid development of electrochemiluminescence (ECL) sensors, more luminophores have been designed to achieve high-throughput and reliable analysis. Abstract : In recent years, with the rapid development of electrochemiluminescence (ECL) sensors, more luminophores have been designed to achieve high-throughput and reliable analysis. Impressively, after the proposed fantastic concept of "aggregation-induced electrochemiluminescence (AIECL)" by Cola, the application of AIECL emitters provides more abundant choices for the further improvement of ECL sensors. In this review, we briefly report the phenomenon, principle and representative applications of aggregation-induced emission (AIE) and AIECL emitters. Moreover, it is noteworthy that the cases of AIECL sensors for bioanalytical detection are summarized in detail, from 2017 to now. Finally, inspired by the applications of AIECL emitters, relevant prospects and challenges for AIECL sensors are proposed, which is of great significance for exploring more advanced bioanalytical detection technology.